The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1002/jhm.600
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of lactic acidosis: Appropriate confusion

Abstract: Lactic acid is a marker of tissue ischemia but it also may accumulate without tissue hypoperfusion. In the latter circumstance, lactic acid accumulation may be an adaptive mechanism-a novel possibility quite in contrast to the traditional view of lactic acid as only a marker of tissue ischemia. Studies on the treatment of LA with sodium bicarbonate or other buffers fail to show consistent clinical benefit. Severe acidemia in the setting of LA is a particularly poorly studied area. In the settings of medication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 126 publications
0
25
0
1
Order By: Relevance
“…This is of special importance in sepsis and shock, where acid accumulation can occur, despite adequate oxygen delivery [46]. Hypermetabolic conditions are observed in shock states like septic shock that are characterized by insulin resistance, hyperlactatemia, and increased oxygen demand, resulting from both enhanced mitochondrial oxygen utilization and oxygen radical production, which may coincide both with compromised tissue microcirculatory perfusion and mitochondrial dysfunction [47].…”
Section: Acidosis Results From Excessive Aerobic Metabolismmentioning
confidence: 99%
“…This is of special importance in sepsis and shock, where acid accumulation can occur, despite adequate oxygen delivery [46]. Hypermetabolic conditions are observed in shock states like septic shock that are characterized by insulin resistance, hyperlactatemia, and increased oxygen demand, resulting from both enhanced mitochondrial oxygen utilization and oxygen radical production, which may coincide both with compromised tissue microcirculatory perfusion and mitochondrial dysfunction [47].…”
Section: Acidosis Results From Excessive Aerobic Metabolismmentioning
confidence: 99%
“…The use of sodium bicarbonate to correct lactic acidosis remains controversial because sodium bicarbonate can increase lactate production14. Recent studies have suggested that therapy be guided by changes in lactate level15.…”
Section: Discussionmentioning
confidence: 99%
“…Four PD solutions were used each day: two 1.5% PhysionealTM PD solutions, one 4.25% PhysionealTM PD solution, and one overnight exchange using 7 We hypothesized that lactate-containing PD solution was one of the causes of her lactic acidosis.…”
Section: Casementioning
confidence: 99%